2009
DOI: 10.1177/0272989x09341588
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Preferences for Treatment of Hepatitis C

Abstract: Background-The objective of this study was to ascertain patient preferences for treatment of HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Consistent with a large amount of literature describing patient preferences for different health care decisions, we found that subjects varied in their preferences for CRC screening tests [33][34][35][36] . What is surprising and interesting in our population is that despite high levels of satisfaction with prior colonoscopy, a significant proportion of patients would choose colon capsule or CT colonography over colonoscopy.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with a large amount of literature describing patient preferences for different health care decisions, we found that subjects varied in their preferences for CRC screening tests [33][34][35][36] . What is surprising and interesting in our population is that despite high levels of satisfaction with prior colonoscopy, a significant proportion of patients would choose colon capsule or CT colonography over colonoscopy.…”
Section: Discussionsupporting
confidence: 83%
“…Fraenkel and colleagues[12] found that HCV-infected patients who perceived higher benefits of treatment were much more willing to accept treatment-related side effects. Similarly, Hauber and colleagues[11] found that increases in the rate of SVR were more than twice as important to patients as avoiding days with flu-like symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…While some evidence of patient preferences regarding HCV treatments exists,[11,12] the available literature focuses on treatment with ribavirin plus interferon or peginterferon. In this paper, we report the results of a choice-format conjoint analysis survey that asked patients to choose among alternative, hypothetical HCV treatments that include characteristics of new DAAs.…”
Section: Introductionmentioning
confidence: 99%
“…'Self-explicated approaches' (SEAs) is a subgroup of stated preference methods that originated in product development and marketing and have become popular due to their ability to determine relative weights for a large number of outcomes with low cognitive burden, small expenses, and relatively undemanding design, analysis and interpretation compared with other methods [20,21]. Research trials applying SEA methods have started to appear in healthcare, and early results indicate that the approaches might be feasible in patients with diverse conditions, including schizophrenia [22][23][24].…”
Section: Introductionmentioning
confidence: 99%